1001 Atraumatic Bilateral Compartment Syndrome; A Case Report. (12th October 2021) - Warren, M; Dhillon, G; Abdulkarim, A
Abstract: Introduction: We present a rare case of lower leg atraumatic bilateral compartment syndrome (ABCS). To date there have only been three similar cases reported where no cause was identified. Case Study: A 33-year-old male presented 12 hours following sudden onset lower leg pain. There was no history of trauma, drug, or alcohol use. On assessment he was in significant pain, not relieved by analgesia, and had clinically tense anterior compartments bilaterally. Both feet were held in fixed dorsiflexion. Creatinine kinase (CK) was 35, 166 on admission. X-rays of both legs were normal. He was immediately taken to theatre for bilateral four compartment fasciotomies which revealed significant swelling in the anterior and lateral compartments with patchy pre-necrosis. Post-operatively he deteriorated, required intubation, and was admitted to ITU for acute haemofiltration to treat acute kidney injury secondary to rhabdomyolysis. Multiple operations were required for debridement, resulting in exposed tendons. Closure of the medial wounds was achieved primarily as an inpatient and he was discharged with bilateral lateral VAC dressings in situ. Lateral wounds were closed with Biodegradable Temporising Matrix followed by split skin grafting. In his second admission he suffered a pulmonary embolism. Literature Review and Discussion: 20 case of ABCS have been reported, largely attributable to drugs, alcohol, or leg position. Most cases had an element of diagnostic delay. In addition to compartment pressure monitoring, testing CK can demonstrate muscle necrosis and supports the decision to proceed to surgery.